PROFILE OF PATIENTS AT RISK FOR CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) BASED ON PUMA SCORE IN SIX COMMUNITY HEALTH CENTERS IN MALANG CITY - Djajalaksana, Susanthy; Wardoyo, Arinto; Muarif, Husnul; Sari, Fitri; Listyoko, Aditya; Lyono, Albert; Pratiwi, Eka; Fahmi, Kristia; Muhammad, Iqbal; Falyani, Silvy; Prasetyo, Kevin; Christanto, Anthony (Journal of Community Health and Preventive Medicine, 2025)
Chronic Obstructive Pulmonary Disease (COPD) is a growing global health problem. Early screening and a deeper understanding of the risk patient profile are critical for effective management. This study aims to analyze the profiles of patients at risk for COPD based on PUMA scores and FEV1/FVC results from six public health centers in Malang City. This study used an analytical-observational design with a cross-sectional approach. Samples were purposefully selected from patients at risk of COPD in six public health centers in Malang. PUMA scores were measured using a questionnaire. Data was collected from November 2022 to April 2023 at six public health centers in Malang City. A total of 117 research subjects participated, comprising 58.97% male and 41.02% female, with an average age of 47 years. Most subjects were active smokers (43.50%). Based on PUMA scores (cutoff >6), 22.03% were at risk of COPD, while 77.97% were not at risk. FEV1/FVC results were >0.7 in 71 subjects (60.68%) and <0.7 in 46 subjects (39.31%). Among subjects at risk of COPD, 92% had FEV1/FVC < 0.7. There were 117 subjects screened for the early detection of COPD. The results of the PUMA* score can help health practitioners in identifying patients at risk of COPD.